ISLAMIC STOICISM AND HUMAN CONSTRUCTIVITY: STRATEGY TO ACHIEVE PEACE IN LIFE AS AN EFFORT TO ACHIEVE WORLD PEACE - Halimah, Siti; safiudin, Khamdan (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research article aims to show that actions that refer to the principles of stoicism in the context of Islam can lead to a peaceful life without any pressure from outside or from within. This life is filled with wisdom in various aspects and sectors of human self-control development. The author raises this issue because Islam is considered the strongest foundation in efforts to revitalise world peace by combining the teachings of the Qur'an with the perspective of stoicism related to Islamic teachings. In addition, attention to this topic is minimal in scientific research and popular articles. The research method used is qualitative, with library research as the primary approach. This process involves a series of activities, including collecting data from literature, reading, recording, and processing research materials. In this article, the author also identifies several principles of stoicism that can help achieve a peaceful and happy life. The integration of this concept provides a holistic view of a lifestyle that supports tranquillity and contributes to the realisation of world peace.